E-commerce System Security Assessment based on Bayesian Network Algorithm Research - Xin Li; Ting Li (Institute of Advanced Engineering and Science, 2013)
Evaluation of e-commerce network security is based on assessment method Bayesian networks, and it first defines the vulnerability status of e-commerce system evaluation index and the vulnerability of the state model of e-commerce systems, and after the principle of the Bayesian network reliability of e-commerce system and the criticality of the vulnerabilities were analyzed, experiments show that the change method is a good evaluation of the security of e-commerce systems. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1905